Structural and chemical investigation of the gel-derived bioactive materials from the SiO2–CaO and SiO2-CaO-P2O5 systems. Issue 15 (15th October 2017) - Zagrajczuk, Barbara; Dziadek, Michal; Olejniczak, Zbigniew; Cholewa-Kowalska, Katarzyna; Laczka, Maria
Abstract: A series of biomaterials from the binary SiO2 –CaO and ternary SiO2 -CaO-P2 O5 systems were obtained by the sol-gel route in the form of powders. The CaO/SiO2 molar ratio, of the samples varied from 1:4 to 3:2. The effect of chemical composition on the structure was investigated with XRD diffraction and FTIR spectroscopy. The presence and relative contribution of silicon Q n (Si) and phosphorus Q n (P) structural units was determined by 29 Si and 31 P MAS NMR. For all of the materials theoretical and NMR network connectivity were calculated. Optical basicity and group basicity theories enabled determination of dependencies between particular types and amounts of Q n (Si) and Q n (P) units. The textural parameters of the powders were determined with the BET. Our studies revealed an increased tendency for crystallization with increasing amount of calcium, in both binary and ternary materials. 29 Si MAS NMR spectra revealed that silicon was present in Q 2, Q 3 and Q 4 structural units. Moreover, 31 P MAS NMR indicated that phosphorus exist mainly as a monophosphate Q° complex. Results shown that calcium induced structure de-polymerization in binary materials, while in ternary system the formation of phosphorus-rich clusters binding calcium were formed, and re-polymerization of silica network took place. Assessment of the biomaterials dissolution and ion release is crucial in terms of further medical applications. Materials solubility expressed as a Ca and Si ion release was measured with the ICP-OES spectrometry. It showed that Ca ions release was more chemical composition dependent, while in contrary the Si release, depended more on the materials textural parameters and crystallinity.